Nitrogen and Phosphorous Content in Blue Mussels (Mytilus spp.) Across the Baltic Sea - Buer, Anna-Lucia; Taylor, Daniel; Bergström, Per; Ritzenhofen, Lukas; Klemmstein, Annemarie (Frontiers in Marine Science, 2020)
To support the ongoing discussion about mussel farming and the potential to extract nutrients from the sea, this study investigated the phosphorus (P) and nitrogen (N) content of blue mussels (Mytilus spp.) under different abiotic and biotic parameters. The focus of this survey was on the highly eutrophied Baltic Sea, where salinity ranges from 4 to 27 psu, and is a major contributing factor to differential mussel growth. We observed that nutrient content was not linearly correlated to salinity, but if categorized, decreased at higher salinities. Chlorophyll-a and temperature did not significantly correlate with nutrient content, but season of harvest and mussel size did. Furthermore, habitat was a strong driver of nutrient content, indicating higher nutrient density if mussels are grown in mussel farms (i.e. in the water column) instead of on mussel culture beds or harvested from wild beds (on the sea bed). Values of N and P averaged 5.85 % N and 0.83 % P of tissue dry weight in mussels at the sea bed and 9.43 % N and 0.96 % P of tissue dry weight in mussels from longline cultivation. These results will be useful in refining estimations about mussel farming as a nutrient mitigation measure and the extraction potential, as well as related costs.